Muscle function and architecture in children with juvenile idiopathic arthritis. (18th May 2020) - Bourdier, Pierre; Birat, Anthony; Rochette, Emmanuelle; Doré, Éric; Courteix, Daniel; Dutheil, Frédéric; Pereira, Bruno; Ratel, Sébastien; Merlin, Etienne; Duché, Pascale
Abstract: Aim: To assess muscle function and functional abilities in children with juvenile idiopathic arthritis (JIA). Methods: Fourteen children with JIA and 14 healthy controls matched for age and sex were included. Muscle characteristics, both structural (thickness, cross‐sectional area (CSA) and fascicle angle) and qualitative (intermuscular adipose tissue; IMAT), were assessed in thigh muscles using ultrasound and peripheral quantitative computed tomography (pQCT). Muscle function and functional abilities were determined from the assessment of maximal voluntary isometric contraction (MVIC) knee extensors force and vertical jump performance. Results: No significant difference in MVIC force was observed between the two groups. However, squat jump height was significantly reduced in children with JIA (18.3 ± 5.4 vs 24.3 ± 7.9 cm, P  < .05). No differences in structural parameters were observed, but IMAT/CSA (0.22 ± 0.02 vs 0.25 ± 0.03; P  = .01) was significantly lower in children with JIA than in healthy children. Conclusion: Knee extensor muscle architecture and force were comparable between children with and without JIA, but functional abilities (vertical jump performance) were poorer in JIA. The lower IMAT area in JIA could result from a lower physical activity level compared with healthy children.